Idiopathic intracranial hypertension without papilledema in chronic migraineurs and revisiting of friedman’s diagnostic criteria - Islam El Malky; Wael Elshazly Aita; Hazem Abdelkhalek; Amr M. Tayel; Mahmoud Abdelhafiz (Scientific Reports)
Abstract The application of Friedman’s criteria to diagnose suggested IIH WOP will prevent many chronic patients with migraine (CM) from proper diagnosis and treatment. Our prospective study aimed to compare the prevalence of suggested IIH WOP in case of following Friedman’s criteria and in case of novel proposed criteria (OP > 200 mmH2O and radiological finding ≥ two), also reporting the predictive radiological signs for IIH WOP. Refractory chronic patients with migraine underwent ophthalmologic, neurological evaluation, MRI, and a lumbar puncture (LP) with opening pressure (OP) measurement. CSF withdrawal was performed in patients with CSF OP > 200 mmH20. Suggested IIHWOP was defined according to Friedman’s criteria and our novel criteria. Regression analysis was performed to detect the strongest predictor of suggested IIHWOP. The effect of CSF withdrawal was evaluated clinically after two months. One hundred and two consecutive CM were enrolled (95 F, age 32.34 ± 9.45, and BMI 29.04 ± 5.89) without papilledema. Eighteen patients (17.65%) had OP greater than 250 mmH2O, and 20 patients (19.61%) with OP ≥ 200 mmH2O and ≤ 250 mH2O. Prevalence of suggested IIH WOP, according to Friedman’s diagnostic criteria, was three patients (2.9%) only. In case of our novel diagnostic criteria (Absent 6th nerve palsy, ICP > 200 mmH2O, and ≥ two radiological signs), eight patients (7.8%) were discovered. After CSF withdrawal, 85% of patients with migraine with OP > 200 mm H2O improved, specially CM with bilateral Transverse sinus stenosis (TSS). The prevalence of suggested IIH WOP in CM was 7.8%. Bilateral TSS was the only predictor of IIHWOP.